Catalan Conflict: Caracter, Dynamics, Interpretations - S. M. Khenkin (Vestnik MGIMO-Universiteta)
Book review: The (des)lace of Catalonia in Spain. 2021. Director Jaime Ferri Durá. Valencia, Tirant lo Blanch. 304 p. ISBN: 978-84-1355-691-8